2001
DOI: 10.1038/sj.bjp.0703761
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet action of R‐99224, an active metabolite of a novel thienopyridine‐type Gi‐linked P2T antagonist, CS‐747

Abstract: 1 CS-747 is a novel thienopyridine-type platelet ADP inhibitor which lacks in vitro activity. This study examined pharmacological pro®les of R-99224, a hepatic metabolite of CS-747. 2 R-99224 produced a concentration-dependent inhibition of in vitro platelet aggregation in washed human platelets (0.03 ± 1 mg ml 71 ), which was relatively speci®c to ADP compared to collagen and thrombin. ) also inhibited the ADP-induced decrease in cyclic AMP levels in PGE 1 -stimulated platelets, whereas the agent did not aect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 27 publications
3
91
0
2
Order By: Relevance
“…Preclinical studies indicate that like clopidogrel, prasugrel is a prodrug that requires metabolic conversion to an active metabolite [19]. Following oral dosing of prasugrel, there is a rapid and potent inhibition of ADP-induced platelet activation and aggregation [19,22,23]. These early studies demonstrated that the dose required to achieve a given degree of platelet inhibition or inhibition of thrombus formation in preclinical models was approximately one-tenth and one-hundredth that of clopidogrel and ticlopidine, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preclinical studies indicate that like clopidogrel, prasugrel is a prodrug that requires metabolic conversion to an active metabolite [19]. Following oral dosing of prasugrel, there is a rapid and potent inhibition of ADP-induced platelet activation and aggregation [19,22,23]. These early studies demonstrated that the dose required to achieve a given degree of platelet inhibition or inhibition of thrombus formation in preclinical models was approximately one-tenth and one-hundredth that of clopidogrel and ticlopidine, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a novel thienopyridine P2Y 12 inhibitor, prasugrel (CS-747, LY640315), has been identified and profiled [19][20][21][22][23]. Preclinical studies indicate that like clopidogrel, prasugrel is a prodrug that requires metabolic conversion to an active metabolite [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recently, it was shown that cytochrome P-450, isoform 3A4 (CYP3A4), is primarily responsible for the metabolism and activation of clopidogrel in vivo. 2 Several studies have shown that clopidogrel decreases the incidence of coronary artery stent thrombosis and is approved for reduction of myocardial infarction, stroke, and vascular death in patients with atherosclerotic vascular disease. 3 Patients with symptomatic coronary artery disease and hypercholesterolemia are frequently given clopidogrel in conjunction with the HMG-CoA inhibitors (statins).…”
mentioning
confidence: 99%
“…Another antiplatelet drug, CS-747, neutralizes P2Y 12 by the same mechanism [76,77]. P2Y 12 also is irreversibly antagonized by the thiol reagent pCMBS [69,78].…”
Section: The P2y 12 Receptormentioning
confidence: 99%